Optimalisasi Produk Mocaf melalui Diversifikasi dan Inovasi Alat Produksi di Desa Pangebatan - Fiby, Fiby; Luzi Dwi Oktaviana; Faridatun Nida; Zanuar Rifai (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2025)
Pangebatan Village has abundant natural resources, namely cassava. Processing cassava into Mocaf flour is one of the innovations that has been carried out, but it turns out that this does not make mocaf flour sell well in the market so that further processing is needed into derivative products that have high selling power including noodles, brownies, and cookies, but limited tools are a factor inhibiting the processing of mocaf flour. In addition, the lack of Human Resources to carry out promotion and marketing is something that needs serious attention. The Lecturer Team of Amikom Purwokerto University together with the PKK Mothers of Pangebatan Village carried out community service activities with the aim of solving several of these problems through the provision of tools to training in making derivative products, namely noodles, brownies, and cookies to digital marketing training to help promote and market products. The Lecturer Team and Students routinely monitor and evaluate community service activities to ensure the right solution for partners, encourage sustainable production of mocaf derivatives by the PKK Mothers of Pangebatan Village to improve family economy, and ensure the continuity of product promotion and sales. Community service activities in 2025 are funded by the Ministry of Education, Culture, Research and Technology as one form of the Tri Dharma of Higher Education to help with the problems of the surrounding community.